2017
DOI: 10.1038/s41598-017-10240-1
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of C-type Natriuretic Peptide in Endothelial Cells Protects against Insulin Resistance and Inflammation during Diet-induced Obesity

Abstract: The endogenous peptide C-type natriuretic peptide (CNP) binds its receptor, guanylyl cyclase B (GCB), and is expressed by endothelial cells in diverse tissues. Because the endothelial cells of visceral adipose tissue have recently been reported to play a role in lipid metabolism and inflammation, we investigated the effects of CNP on features of obesity by using transgenic (Tg) mice in which CNP was placed under the control of the Tie2 promoter and was thus overexpressed in endothelial cells (E-CNP). Here we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 67 publications
0
19
0
1
Order By: Relevance
“…Во-вторых, сосудистый эндотелий имеет морфологические и функциональные вариации, подходящие под конкретное местонахождение в организме [38]. Сосудистый эндотелий продуцирует большое количество биологически активных веществ от неорганической молекулы NO до сложных органических структур (эндотелиальный натрийуретический пептид C-типа) [39,40]. Таким образом, СЭ является не только барьерным слоем клеток между кровью (или лимфой) и субэндотелиальными сосудистыми тканями, но и активным эндокринным «органом», который участвует в функциональной саморегуляции, регенерации и ремоделировании сосудистого русла, в непосредственном метаболизме тканей и органов, трансваскулярной миграции веществ и клеток, например лейкоцитов, а также влияет на важнейший этап работы системы гемостаза -коагуляцию [41][42][43].…”
Section: сосудистый эндотелийunclassified
“…Во-вторых, сосудистый эндотелий имеет морфологические и функциональные вариации, подходящие под конкретное местонахождение в организме [38]. Сосудистый эндотелий продуцирует большое количество биологически активных веществ от неорганической молекулы NO до сложных органических структур (эндотелиальный натрийуретический пептид C-типа) [39,40]. Таким образом, СЭ является не только барьерным слоем клеток между кровью (или лимфой) и субэндотелиальными сосудистыми тканями, но и активным эндокринным «органом», который участвует в функциональной саморегуляции, регенерации и ремоделировании сосудистого русла, в непосредственном метаболизме тканей и органов, трансваскулярной миграции веществ и клеток, например лейкоцитов, а также влияет на важнейший этап работы системы гемостаза -коагуляцию [41][42][43].…”
Section: сосудистый эндотелийunclassified
“…It was suggested that CNP overexpression in adipocytes protects against adipocyte hypertrophy, excess lipid metabolism, inflammation, and decreased insulin sensitivity during HFD-induced obesity. An earlier report also suggested that overexpression of endothelialspecific CNP overexpression protects against visceral adipose tissue hypertrophy, systemic inflammation, and insulin resistance during the development of obesity due to the feeding of a high-fat diet (HFD) [99]. Overall current knowledge suggests that natriuretic peptides are new pathways controlling human adipose tissue lipolysis operating via a cGMP-dependent pathway.…”
Section: Other Conditions In Which Circulating Cnp Levels Are Affectedmentioning
confidence: 99%
“…Natriuretic peptides (NPs), which include atrial NP (ANP), brain NP (BNP), and C-type NP (CNP), are associated with obesity, insulin resistance, and metabolic syndrome 4 7 . In particular, C-type NP (CNP) is an endogenous peptide that binds its receptor guanylyl cyclase B (GCB) 8 , 9 , thus inducing cGMP production 10 .…”
Section: Introductionmentioning
confidence: 99%
“…CNP is locally produced and acts as an autocrine–paracrine regulator 14 that is expressed in a wide variety of tissues, including brain, lung, heart, kidney, bone, and endothelium. We recently revealed that CNP and GCB are expressed in adipose tissue 7 . Transgenic (Tg) mice with endothelial cell-specific overexpression of CNP are protected against visceral adipose tissue hypertrophy, systemic inflammation, and insulin resistance during the development of obesity due to feeding of a high-fat diet (HFD) 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation